Therapeutic lymphangiogenesis after myocardial infarction: vascular endothelial growth factor-C paves the way - Goichberg, Polina (Journal of Thoracic Disease, 2016)
The new excellent study by Henri and colleagues published in the April 12 issue of the Circulation journal addresses an important issue of the involvement of lymphatic vasculature in the restoration of cardiac function after infarction (1).